A review of subcritical water as a solvent and its utilisation for the processing of hydrophobic organic compounds - Carr, A.; Mammucari, R.; Foster, Neil (Elsevier BV, 2011)
The popularity of using subcritical water as a solvent to extract a variety of organic compounds has grown over the last 10 years. A number of review articles have identified subcritical water as an effective solvent, catalyst and reactant for hydrolytic conversions and extractions [1]. The aim of this paper is to review the literature that describes subcritical water purely as a solvent for solubilizing HOCs. The literature reviewed includes publications on subcritical water extraction, publications on the measurement of the solubility of organic compounds in subcritical water, the use of the solubility data in solubility modelling and a recently developed particle formation technique. © 2011 Elsevier B.V.